Customer satisfaction of credit card services - Goh, Eng Beng (2014)
This study aims to identify the key attributes of credit card services which appeal to consumers. In view of the highly competitive nature of the credit card market, the ability to isolate the dominating factors is essential in meeting consumers' needs. Resources can then be optimally utilised and issuers can better tailor their services not only towards retaining existing customers but also to attract potential ones.